EFFECTS OF CULTURE CONDITIONS ON THE PRODUCTION OF ENDO-p-1,4-GLUCANASE BY ASPERGILLUS AWAMORI VTCC-F-099 - Tuân, Nguyễn Văn; Thi, Quyền Đình (Vietnam Journal of Biotechnology, 2011)
Cellulases are a group of hydrolytic enzymes and are capable of degrading lignocellulosic materials. These enzymes are produced by several microorganisms including bacteria and fiingi. Endo P-l,4-glucanase is one of three types cellulase, which has a wide range of applications such as in food, animal feed, pulp industry, waste management, etc. Aspergillus awamori VTCC-F-099 (A. awamori VTCC-F-099) strain produced the highest amount of endo )3-l,4-glucanase (CMCase) among 26 A. awamori strains were screened. Some culture conditions for A. awamori VTCC-F-099 strain producing CMCase were examined to assess their effect on enzyme production. CMCase production ofthe strain A. awamori VTCC-F-099 was the highest after 96 hours of fermentation in MTI medium with 2% CMC. The optimum temperature and pH for CMCase production from the strain A. awamori VTCC-F-099 were 30°C and 6.5, respectively. The strain A. awamori VTCC-F-099 produced CMCase highest in case the corncob used as carbon source (3.0%) among tested carbon sources (lactose, glucose, saccharose, sugar-cane bagasse, coffee grounds, rice brand, corncob, peanut shell, dried mandarin shell, saw dust, coconut fiber). Ammonium acetate (0.3%) was the best nitrogen source for the strain A. awamori VTCC-F-099 producing highest CMCase among tested nitrogen sources (peptone, urea, fish powder, soybean powder, casein, CH3COONH4, NH4NO3, (NH4)2S04).